2015
DOI: 10.1103/physrevb.91.195204
|View full text |Cite
|
Sign up to set email alerts
|

Collective magnetization dynamics in ferromagnetic (Ga,Mn)As mediated by photoexcited carriers

Abstract: We present a study of photo-excited magnetization dynamics in ferromagnetic (Ga,Mn)As films observed by time-resolved magneto-optical measurements. The magnetization precession triggered by linearly polarized optical pulses in the absence of an external field shows a strong dependence on photon frequency when the photo-excitation energy approaches the band-edge of (Ga,Mn)As. This can be understood in terms of magnetic anisotropy modulation by both laser heating of the sample and by hole-induced non-thermal pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Figure 1 shows a typical magnetization precession response to such a pulse at 10 K for the annealed (Ga,Mn)As sample excited by a linearly-polarized pump beam at 1.58 eV. As shown in Figure 1a, the temporal evolution of the photoexcited magnetization observed by time-resolved magneto-optical measurement in ferromagnetic (Ga,Mn)As can be fitted by an exponentially damped sine function superimposed on a pulse-like function [7,21],…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Figure 1 shows a typical magnetization precession response to such a pulse at 10 K for the annealed (Ga,Mn)As sample excited by a linearly-polarized pump beam at 1.58 eV. As shown in Figure 1a, the temporal evolution of the photoexcited magnetization observed by time-resolved magneto-optical measurement in ferromagnetic (Ga,Mn)As can be fitted by an exponentially damped sine function superimposed on a pulse-like function [7,21],…”
Section: Resultsmentioning
confidence: 97%
“…Earlier studies reported that the pulse-like signal which persists above the Curie temperature is related to the recovery process of nonequilibrium electron-hole pairs in the GaAs substrate [10,28], and only the oscillatory part is directly related to the ferromagnetic order of (Ga,Mn)As [12]. The numerical fitting result by the Landau-Lifshitz-Gilbert (LLG) equation shown in Figure 1b is focused on the precession part of the observed Kerr rotation, which reflects the uniform precession of magnetization in the annealed (Ga,Mn)As film [21]. The collective spin excitation and modulation of the dynamics of precession discussed below will mainly focus on the characteristics of the oscillatory signal modulated by laser excitation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations